TRANSFORMATION OF ACADEMIC LIBRARY SERVICES AS A COLLABORATIVE SPACE FOR STUDENTS AT UINSU (International Journal of Cultural and Social Science, 2026)
This study examines the transformation of academic library services at UINSU Campus IV Tuntungan as a collaborative learning space and its contribution to strengthening the social solidarity of Library Science students. The main problem addressed in this research is the shifting role of academic libraries from conventional information providers to learning commons that facilitate academic interaction, collaborative learning, and social connectedness among students. This study employed a descriptive qualitative approach. Data were collected through observation, semi-structured interviews, and documentation involving librarians, library staff, and Library Science students who actively used library services. The findings show that the transformation of library services is reflected in three main aspects: spatial transformation through open and flexible learning areas, service transformation through user-centered facilities, and social transformation through increased academic interaction among students. Students used the library not only to access references but also to conduct group discussions, complete collaborative assignments, carry out research interviews, and build interpersonal relationships. These activities encouraged mutual assistance, academic communication, and a stronger sense of togetherness among students. The novelty of this study lies in its integration of the learning commons concept with the analysis of students’ social solidarity in the context of an academic library. This research concludes that academic libraries play a strategic role not only as information centers but also as collaborative and inclusive academic social spaces that support learning productivity, digital access, and student social cohesion.